Aphids affecting subtropical Argentina strawberry production: species, cultivar preference, and nation-wide distribution update - Maza, Noelia; Kirschbaum, Daniel Santiago; Mazzitelli, Emilia; Figueroa, Pablo Matías; Villaverde, J.; Funes, Claudia Fernanda (Ediciones INTA, 2024)
Argentina accounts for ~2,000 ha of strawberries (Fragaria x ananassa Duch.) and produces ~70,000 t, being aphids a relevant pest. The objectives of this study were to survey aphid species in a strawberry crop located in subtropical Argentina, along with their varietal preference and impact on plant productivity, and to update the distribution of aphid species throughout strawberry growing regions. The study was conducted in Tucumán province, where fresh-dug plants of different strawberry cultivars (‘Benicia’, ‘Cabrillo’, ‘Camino Real’, ‘Fronteras’, ‘Merced’, ‘Petaluma’ and ‘San Andreas’) were grown in an annual production system. In 2018, plant plots were randomly monitored every 14-15 days in July, August (winter), September and October (spring) for aphid presence. Once the presence of aphid colonies was confirmed, individuals were collected and identified. For fruit production evaluations, berries were harvested from June to December. Eight aphid species were identified: Aphis forbesi (first record in strawberries in Tucumán), Aphis gossypii (largest colony number), Aphis sp., Chaetosiphon fragaefolii, Chaetosiphon sp., Macrosiphum euphorbiae, Myzus persicae, and Rhodobium porosum. The largest number of aphids was collected in winter. All strawberry cultivars were infested by aphids; however, not all aphid species were found in all cultivars. ‘Fronteras’ was attacked by the eight aphid species found, while ‘Benicia’ and ‘Camino Real’ by seven, ‘Cabrillo’ and ‘Merced’ by four, and ‘Petaluma’ and ‘San Andreas’ by three. Most of the specimens were collected during the winter. There was no evident influence of the varietal preference of aphids on cultivar fruit production and quality. ‘Fronteras’ and ‘Camino Real’ were infested by eight different aphid species, but the first one had the highest yield of the trial, while the second one had the lowest. No virus symptoms were recorded in the sampled plots. According to these results, there are 13 aphid species recorded in Argentina and they belong to seven genera: Aphis (4), Chaetosiphon (3), Myzus (2), Aulacorthum (1), Cryptomyzus (1), Macrosiphum (1), and Rhodobium (1), all distributed in nine strawberry growing provinces.